2007
DOI: 10.1002/ijc.22712
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous phenotype and MC1R variants as modifying factors for the development of melanoma in CDKN2A G101W mutation carriers from 4 countries

Abstract: The G101W founder mutation is the most common CDKN2A mutation in Italy, Spain, and France. As the background of modifying genes, environmental exposures, and sun behavior vary across countries, studying G101W carriers from distinct countries offers a unique opportunity to evaluate possible modifying factors in melanoma development. We evaluated 76 G101W cases and 59 carrier controls from France, Italy, Spain, and the United States. Hair color and dysplastic nevi distributions differed significantly in cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
4
39
2
Order By: Relevance
“…The results of this study confirm previous findings in our population, showing that Italian CDKN2A+ CM cases have substantially fewer MC1R variants than cases from other geographic areas and that Italian cases do not show an association between MC1R and CM risk (17,21). Our findings suggest that other genes, besides MC1R, may modify CM risk in CDKN2A + cases and that MC1R plays a role in CM development in CDKN2AÀ cases both via pigmentary and non-pigmentary pathways.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study confirm previous findings in our population, showing that Italian CDKN2A+ CM cases have substantially fewer MC1R variants than cases from other geographic areas and that Italian cases do not show an association between MC1R and CM risk (17,21). Our findings suggest that other genes, besides MC1R, may modify CM risk in CDKN2A + cases and that MC1R plays a role in CM development in CDKN2AÀ cases both via pigmentary and non-pigmentary pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Separate observation of data from the Italian families we contributed did not show the association (21), confirming the results of a previous study on carriers of the common CDKN2A G101W founder mutation, which showed an impact of MC1R variants on CM risk in G101W carriers from Spain, France and the United States but not in G101W carriers from Italy (17).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…To date, no clinical, dermoscopic, or histopathological special feature has been related to tumours in FamMM (5)(6)(7). Polymorphisms in melanocortin I receptor (MCIR) gene, especially the red hair variants (RHV), are considered low susceptibility genes to MM development, increasing the MM risk up to 10 times in respect to wild type (8). We studied the interaction between these lowrisk variants among FamMM cases, and found that they can increase the genetic risk in CDKN2A (high-risk gene) mutation carriers by up to 14 times and contribute to a less suspicious clinical and dermoscopic appearance of tumours, less colour, and fewer structures (9).…”
mentioning
confidence: 99%
“…Regarding GSTP1, heterozygous and homozygous for the less frequent allele were pooled since there were few (p.I105V variant) or none (p.A114V variant) homozygous subjects. Since the risk of melanoma was found to increase with the number of MC1R variants in various populations including ours [21], a MC1R variable was created by assigning subjects to one of the three following categories: MC1R consensus homozygous subjects vs. subjects with one MC1R variant vs. subjects with at least two MC1R variants. A RHC variable (pooling the red hair and fair skin associated variants i.e., p.R151C, p.R160W, p.D84E and p.D294H) and a NRHC variable (pooling all non-synonymous non-RHC variants) were also considered.…”
Section: Data Codingmentioning
confidence: 99%